Analisis Manajemen Risiko Pada UMKM “Sempol Ayam Si Kabayan” Bandung - Nur Zaman, Luqman; Sheehan, Sheva Dhaifullah; Andryanti Natanegara, Aura Syahida (Universitas Serambi Mekkah, 2024)
UMKM Sempol Ayam Si Kabayan in Bandung is a local culinary business that focuses on traditional sempol chicken snack products with distinctive and innovative flavors. This business has attracted the attention of consumers through creative marketing strategies and maintained product quality. However, like many other MSMEs, Sempol Ayam Si Kabayan faces various business risks that can affect the sustainability of its operations. This research analyzes risk management in MSMEs by identifying Market, Financial, Marketing, Operational, Human Resources, Legal risks and evaluating their severity. Based on interview results, it was found that the main risks include fluctuations in raw material prices, labor turnover, dependence on digital marketing, and intense market competition. This research also uses a SWOT analysis approach to evaluate the strengths, weaknesses, opportunities and threats faced by MSMEs. The results show that implementing appropriate risk mitigation strategies, such as better financial management, product diversification, and strengthening customer loyalty, can increase business resilience to changes in the business environment. These findings provide practical contributions to the development of risk management in MSMEs, especially in the processed food sector.